Penyuluhan Bahaya Kandidiasis Sebagai Penyakit Menular Seksual Pada Mahasiswa Tingkat Akhir Poltekkes Kemenkes Aceh - Rahmayanti Rahmayanti; Erlinawati Erlinawati; Siti Hadijah; Darmawati Darmawati; Fitriana Fitriana (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
Sexually transmitted infections have a significant impact on sexual and reproductive health worldwide. Yeast infections are not generally considered sexually transmitted diseases (STDs) because they are caused by an overgrowth of fungi already present in the body. However, sexual activity can sometimes cause this imbalance. The purpose of this community service is to increase the knowledge and understanding of candidiasis among the public, particularly final-year students of the Aceh Ministry of Health Polytechnic of Health. The method used was an outreach method, using visual aids and a questionnaire as an instrument. The target audience was 80 final-year students majoring in TLM at the Aceh Ministry of Health Polytechnic of Health. The activity began with a pre-test followed by a presentation of the activity material. After the presentation, a question-and-answer session was held with participants given the opportunity to ask questions, followed by brochures being distributed, followed by a post-test. Data analysis showed a 95% increase in student knowledge after the outreach. It can be concluded that this outreach activity ran smoothly and successfully, with participants' knowledge increasing after the outreach.